GIVING VERSUS RECEIVING SOCIAL SUPPORT: AN ANALYSIS OF WHAT CONTRIBUTES THE MOST TO FAVORABLE LIFE OUTCOMES - Sultan, Sarwat; Kanwal, Frasat; Gul, Shahzad (PEOPLE: International Journal of Social Sciences, 2017)
This study calls for the question whether providing help to others is more beneficial than receiving it. Thus the present study probed the relative contributions of giving versus receiving social support to life satisfaction, marital satisfaction and distress in a sample of 436 older married adults aged 43-66 years. Baseline indicators of giving and receiving support were used to predict the study variables. Adults also provided data on the measures of life satisfaction, marital satisfaction, and distress. Results from regression analyses indicated that life and marital satisfaction were significantly increased for individuals who reported providing instrumental support to friends, relatives, and neighbors, and individuals who reported providing emotional support to their spouse. Receiving support had no effect on life and marital satisfaction once giving support was taken into consideration. The results pertaining to distress showed the opposite findings for individuals who reported providing support than individuals receiving support. These results have implications for understanding how social contact influences life patterns, happiness, and mental health.